Role of proteoglycans and glycosaminoglycans in Duchenne muscular dystrophy. (19th June 2018) - Carmen, Laurino; Maria, Vadala'; Morales-Medina, Julio Cesar; Vallelunga, Annamaria; Palmieri, Beniamino; Iannitti, Tommaso
Abstract: Duchenne muscular dystrophy (DMD) is an inherited fatal X-linked myogenic disorder with a prevalence of 1 in 3500 male live births. It affects voluntary muscles, and heart and breathing muscles. DMD is characterized by continuous degeneration and regeneration cycles resulting in extensive fibrosis and a progressive reduction in muscle mass. Since the identification of a reduction in dystrophin protein as the cause of this disorder, numerous innovative and experimental therapies, focusing on increasing the levels of dystrophin, have been proposed, but the clinical improvement has been unsatisfactory. Dystrophin forms the dystrophin-associated glycoprotein complex and its proteins have been studied as a promising novel therapeutic target to treat DMD. Among these proteins, cell surface glycosaminoglycans (GAGs) are found almost ubiquitously on the surface and in the extracellular matrix (ECM) of mammalian cells. These macromolecules interact with numerous ligands, including ECM constituents, adhesion molecules and growth factors that play a crucial role in muscle development and maintenance. In this article, we have reviewed in vitro, in vivo and clinical studies focused on the functional role of GAGs in the pathophysiology of DMD with the final aim of summarizing the state of the art of GAG dysregulation within the ECM in DMD and discussing future therapeutic perspectives.